ISOLATION OF ENDOPHYTIC BACTERIA FROM TAXUS ROOT (Taxus sumatrana) AND TEST ITS POTENCY AS PRODUCER OF ANTIMICROBIAL COMPOUNDS - Mulia Mulia; Dwi Hilda Putri; Linda Advinda; Irdawati Irdawati (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
Endophytic bacteria have been extensively studied as a source of new antimicrobial compounds. Research into new antimicrobials is important as an alternative to the treatment of resistant microbes. One potential source of antimicrobial compounds is the Taxus (Taxus sumatrana). This study aimed to investigate the antimicrobial activity produced by the endophytic bacteria of the Taxus. Endophytic bacteria were isolated from the roots of Taxsus plants growing in Mt. Singalang, X Koto District, West Sumatra. Bacteria were isolated by inoculating pieces of Taxus root tissue into a PDA medium. Endophytic bacteria were identified macroscopically and microscopically. Antimicrobial activity was tested with the test microbe using the spot test diffusion method. As a result of the research, 23 isolates of endophytic Taxus bacteria were obtained, of which 21 isolates were gram-positive and 2 isolates were gram-negative bacteria. The results of the antimicrobial activity test yielded only 2 isolates of endophytic bacteria with antibacterial activity.